2018
DOI: 10.1002/mnfr.201700965
|View full text |Cite
|
Sign up to set email alerts
|

Isothiocyanates: Translating the Power of Plants to People

Abstract: Isothiocyanates from cruciferous vegetables have been studied extensively in cells and in animals for their disease preventive and therapeutic effects. However, translating their utility to human populations has been both limited and challenging. Herein, clinical trials employing two isothiocyanates, sulforaphane (SFN; 1-isothiocyanato-4-(methylsulfinyl) butane) and phenethyl isothiocyanate (PEITC; 2-isothiocyanatoethylbenzene) that are isolated principally from broccoli and watercress, respectively, are summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
116
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 96 publications
0
116
0
3
Order By: Relevance
“…Whereas bardoxolone-me was chemically engineered to strongly increase its electrophilicity, plant-derived sulforaphane is a less reactive electrophile obtained from broccoli sprouts upon enzymatic hydrolysis of glucoraphanin by the enzyme myrosinase (57). Large clinical trials have shown that sulforaphane is a promising therapy for preventing liver carcinogenesis induced by aflatoxin in endemic areas of the province of Qidong in China (58).…”
Section: No2-fa Therapy At the Intersection Of Other Successful Pharmmentioning
confidence: 99%
“…Whereas bardoxolone-me was chemically engineered to strongly increase its electrophilicity, plant-derived sulforaphane is a less reactive electrophile obtained from broccoli sprouts upon enzymatic hydrolysis of glucoraphanin by the enzyme myrosinase (57). Large clinical trials have shown that sulforaphane is a promising therapy for preventing liver carcinogenesis induced by aflatoxin in endemic areas of the province of Qidong in China (58).…”
Section: No2-fa Therapy At the Intersection Of Other Successful Pharmmentioning
confidence: 99%
“…Plants produce a myriad of phytochemicals and many of these have valuable nutritive, medicinal and health promoting properties [1][2][3] (Tables 1-3). Anecdotal evidence often points to these beneficial properties however in this report we will concentrate on two members of the glucosinolates (Figure 1), Glucoraphanin and Sinigrin, with a very extensive scientific and nutritional literature illustrating their potential therapeutic applications [3][4][5][6][7][8][9][10][11][12] (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that plants have a well‐evolved stress response mechanism that allows for them to protect themselves against environmental threats . In fact, the glucosinolate–isothiocyanate axis may exist precisely for this purpose in the cruciferous plant—to generate a tightly controlled antipathogenic response, given the potent antibacterial and antifungal properties of isothiocyanates . However, upon formation of these bioactive isothiocyanates, they have to be effectively neutralized and eliminated from plant cells, a process that may include the formation of the inactive metabolite TTCA.…”
Section: Discussionmentioning
confidence: 99%
“…[33,34] In fact, the glucosinolateisothiocyanate axis may exist precisely for this purpose in the cruciferous plant [35] -to generate a tightly controlled antipathogenic response, given the potent antibacterial and antifungal properties of isothiocyanates. [36] However, upon formation of these bioactive isothiocyanates, they have to be effectively neutralized and eliminated from plant cells, a process that may include the formation of the inactive metabolite TTCA. Nevertheless, the exact mechanism by which this isothiocyanate cycling or removal occurs in plants is not well understood.…”
Section: Discussionmentioning
confidence: 99%